24: Season two - Surnow, Joel.; Cochran, Robert; Sutherland, Kiefer, 1966-; Hope, Leslie; Wynter, Sarah, 1973-; Cuthbert, Elisha; Berkeley, Xander, 1955-; Bernard, Carlos; Haysbert, Dennis; Clarke, Sarah, 1972-; Imagine Television (Firm); Real Time Productions (Firm) (Beverly Hills, CA : Twentieth Century Fox Home Entertainment, 2007)
It's been over a year since his wife's death, but Jack Bauer and his daughter are still reeling from the tragedy. The two are estranged and Jack no longer works for CTU. An urgent phone call from the President plunges Jack back into another 24-hour nightmare as he races against time to prevent the detonation of a nuclear bomb in Los Angeles.
Widescreen presentation.
Originally broadcast by Fox during the 2002-2003 season.
Kiefer Sutherland, Leslie Hope, Sarah Wynter, Elisha Cuthbert, Xander Berkeley, Carlos Bernard, Dennis Haysbert, Sarah Clarke.
DVD; Dolby digital surround.
Closed captioned for the hearing impaired.
Language tracks in English, Spanish, with optional subtitles in English and Spanish.
Keywords: Terrorism -- Prevention -- Drama -- DVDs; Threat of violence -- Drama -- DVDs; Video recordings for the hearing impaired; Los Angeles (Calif.) -- Drama -- DVDs